The Effect of Resettlement on Pastoralists’ Livelihood in Somali Regional State: The Case of Hargelle Woreda. - Hirsi, Hibil Hussen; DR. Ali Hassen (IJRDO - Journal of Social Science and Humanities Research, 2019)
This study was conducted to assess and examine the effect of resettlement on resettled pastoralists’ livelihood in Hargelle. In light of this, both primary and secondary data were used. Primary data was obtained through semi-structured questionnaire, key informant interviews, focus group discussions and field observation. Secondary data was obtained from published and unpublished materials, books, journals and project reports. A total of 156 sample respondents were identified using simple random sampling technique. The study finding indicates the improvement of re-settlers’ livelihood (improvement of infrastructure, improvement of basic services and increment of income). The analysis is made at household level on the basis of both inferential and descriptive statistics. The result of multiple-regression analysis showed that the demographic features and livelihood assets had relationship with respondents’ livelihood outcomes. This situation had been observed across all demographic features and livelihood assets of the respondents. The multiple regression analysis also showed that marital status, education level, age of household, gender of household head, land size and TLU were found to be statistically significant related to the livelihood increment of settler population (P<0.05).